Social studies education as a propeller for teaching global intercultural understanding (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This paper examined Social Studies Education as a propeller for teaching global intercultural understanding. The paper discusses social studies education as a propeller for teaching global intercultural understanding by explicitly examining Social Studies Education, propeller, teaching, global, and intercultural understanding. Also, the ideas that propelled the teaching of social studies for intercultural understanding, criteria for the teaching of intercultural understanding, the place of social studies in the promotion of cultural values, as well as social studies content for propelling global intercultural understanding were thoroughly discussed in this study. In order to promote aculture of tolerance, respect for human rights, and justice, intercultural understanding aims to assist the numerous ethnic and linguistic communities that comprise the majority of modern states. In light of the theoretical viewpoints on Social Studies Education and intercultural understanding, this paper addresses the social studies programme's applicability to such curricular reviews and emphasizes the scope and key elements of intercultural understanding as well as the requirements for achieving it. It is recommended in this study that Social Studiescurriculum should be restructured for effective teaching of intercultural understanding and cultural values.
Keywords: Social Studies Education; Propeller; Teaching; Global; Intercultural Understanding